Cinta itu Membutakan: Moderasi Mediasi Pengaruh Sosial dan Brand Ambassador pada Brand Love dan Niat Membeli - Anisah Julia; Kholif Matunni’mah; Nabila Syalsa Yulianti; Resti Hardini (Oikonomia: Jurnal Manajemen, 2022)
PurposeThe purpose of this study is to examine whether the love of a brand perceived by customers affects buying interest, moderated by social influences and mediated by brand ambassadors. MethodologyThis study took the population of the UNIQLO brand clothing customers in Margonda City Depok, West Java. The sample was selected by accidental sampling technique and obtained a total of 100. Data collection through questionnaires. The analysis technique for testing mediation moderation uses Process V3.5 with model no 8. Findings The test results with Macro Process show that the brand ambassador mediates the relationship between brand love and purchase intention. Customers who love the brand do not directly want to buy the product. The better the brand ambassador in the customer's mind, the more customers will intend to buy the product. Meanwhile, the more external social influence factors, the lower the customer's desire to buy the product. Suggestion Manufacturers should be careful in creating good communication channels that portray positive things from brand ambassadors and other communication channels to fortify customers from unfavorable social influences. Love for the brand must always be nurtured.